PeduliLindungi Usability Evaluation Using Usability Scale (SUS) - Kristophorus Hadiono; Agnes Widyaningrum; Uswatun khasanah (SISFORMA, 2024)
Technology advancement is inevitable. During COVID-19 pandemic, Indonesia was like other country, the government try to protect its people and still consider on how the economy can keep running. During that situation, the PeduliLindungi application is developed and used for monitoring and recording of people's healthiness. The PeduliLindungi application was used by broad range of people's, devices, and capabilities. In order to achieved its performance, it raises a need to see the usability of the application. One of popular test on usability is by implement the SUS method. This research got 260 respondents feedback using SUS questionaire and gives results of that fall into "GOOD", "OK", and "POOR" category. The SUS score was 49.24618 which fall into "OK" category. It can be said that the PeduliLindungi application can serve its purposes.